Orientasi Etika Penyuluh Pertanian di Kabupaten Konawe - Salahuddin, Salahuddin; Malik, Nurhayu (AGRITEXTS: Journal of Agricultural Extension, 2024)
This research aimed to analyze the ethical orientation of agricultural extension workers in agricultural extension in Konawe Regency. The research was conducted in Konawe Regency, Southeast Sulawesi Province. The location of this research was determined purposively or deliberately. The respondents of this study were the entire research population, namely all food crop agricultural extension workers who had status as State Civil Apparatus (ASN) in Konawe, with a total 113 people (census). The research variable is the ethical orientation of agricultural extension workers, which includes: idealism and relativism ethical orientation. The data analysis used to describe the ethical orientation of extension workers in agricultural extension is descriptive quantitative using class intervals. The results showed that the ethical orientation of extension workers in agricultural extension in Konawe Regency is in the medium category. Extension workers in Konawe already have a good ethical orientation in agricultural extension, but this needs to be improved so that extension workers have a high or very good ethical orientation in agricultural extension. Agricultural extension workers who have a high ethical orientation will always carry out extension activities professionally.